2020
DOI: 10.1097/brs.0000000000003872
|View full text |Cite
|
Sign up to set email alerts
|

Less is More: Five-item Neck Disability Index to Assess Chronic Neck Pain Patients in Brazil

Abstract: Study Design. Cross-sectional study. Objective. The aim of this study was to assess the structural validity of the Brazilian version of the Neck Disability Index (NDI) in patients with chronic neck pain. Summary of Background Data. NDI is widely used in clinical and scientific contexts, although its structure has not been evaluated in the Brazilian version. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…When comparing the different possible Northwick Park Neck Pain Questionnaire structures, the reduced version with 5 items presented better fitting indexes and lower Akaike information criterion and Bayesian information criterion values. A recently published study has assessed the internal structure of the Neck Disability Index 24 in a similar manner that was performed in the present study. The authors have also found that a 5-item version of Neck Disability Index presented a better structure for this instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the different possible Northwick Park Neck Pain Questionnaire structures, the reduced version with 5 items presented better fitting indexes and lower Akaike information criterion and Bayesian information criterion values. A recently published study has assessed the internal structure of the Neck Disability Index 24 in a similar manner that was performed in the present study. The authors have also found that a 5-item version of Neck Disability Index presented a better structure for this instrument.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazilian Portuguese, some instruments are available to measure disability related to neck pain. However, key measurement properties have not been tested for the Copenhagen Neck Functional Disability Scale; 25 the Neck Disability Index has a contested internal structure; 24 the use of the Neck Bournemouth Questionnaire is not recommended based on its internal structure; 26 and the Profile Fitness Mapping Neck Questionnaire has adequate measurement properties, but is an instrument with many items, 5 turning its application time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Functional status measurement is frequently determined with patient-reported outcome measures (PROMs) as they provide optimal practicality, statistical coherence, and structural-validity [ 1 ]. For patients with spine disorders, there has been a progressive shift toward ‘whole-spine’ PROMs that measure status as a continuous functional kinetic-chain [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative approaches use expert committee consensus with the ‘concept-retention’ method advocated for being judgmental and retaining the original PROMs theoretical domains [ 41 ]. Quantitative approaches use statistical methods, with ‘factorial’ and ‘Rasch’ the most common [ 1 , 41 ]. This study aimed to: 1) develop a shortened-SFI for assessing spine functional status; 2) determine the correlation between the shortened-SFI and whole-spine criteria; 3) assess the correlation between the shortened-SFI and regional-spine, condition-specific, and patient-specific; criteria 4) investigate the correlation between the shortened-SFI and general-health and pain criteria; 5) ensure that the shortened-SFI retains the psychometric characteristics of one-dimensional structural validity, high internal consistency, and no floor/ceiling effect; and 6) enhance the practicality of the shortened-SFI to reduce administrative burden.…”
Section: Introductionmentioning
confidence: 99%
“…Two scales (the modified JOA and NDI scales) were employed to measure disease severity from multiple dimensions, such as symptoms, physical signs, and quality of life. 28 , 29 The occupancy ratio of the spinal canal, which evaluates the space occupied by the ossification, is moderate to highly negatively ( r = –0.66) correlated with the JOA score (higher scores indicate better moto and sensational function) and moderately positively ( r = 0.56) associated with NDI scores (higher scores indicate worse living quality) (Fig. S1g, h ).…”
Section: Resultsmentioning
confidence: 99%